Urgent Endovascular Treatment of Iliac Artery Pseudoaneurysm in Patient with Ehlers-Danlos Syndrome: A Case Report - Gjoreski, Aleksandar; Jovanoska, Ivona; Dungevski, Gjorgi; Lazovski, Nikola; Lazareska, Menka (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Ehlers-Danlos syndrome (EDS) type IV is a heritable disorder of connective tissue that is mainly associated with vascular maladies such as aneurysms, pseudoaneurysms, and dissections with or without spontaneous rupture. Historically, vascular complications in EDS IV have been treated conservatively whenever possible, due to the high morbidity and mortality after vascular interventions, whether open or endovascular. We present a case of a ruptured pseudoaneurysm of the right common iliac artery in a 18-year-old male, who was successfully treated by endovascular approach and later diagnosed with EDS type IV. CASE PRESENTATION: A 18-year-old male patient was admitted in ER with sharp pain in the right hypogastrium, hypotensive and with reduced blood parameters. Multiphasic modern computed tomography (MDCT) scan of abdomen and pelvis revealed massive ride sided pelvic and retroperitoneal hematoma. The presence of pseudoaneurysms on both common iliac arteries (CIA) was detected, with small ulcer on the right side and a focal dissection on the left side. An urgent endovascular repair of the ruptured pseudoaneurysm on the right CIA with covered stent was performed. Patient’s laboratory parameters and clinical status improved significantly within the next few days. CONCLUSIONS: Vascular repair in EDS-IV patients carries significant risk and should be indicated very carefully. Endovascular treatment for these patients is feasible and should be considered as an alternative to open surgery in some challenging cases as this one.